Morpholin-2-one Derivatives via Intramolecular Acid-Catalyzed Hydroamination - Hadi Aldmairi, Abdul; Knight, David W.; Wirth, Thomas (Synthesis, 2019)
Substituted morpholin-2-one derivatives were readily obtained in two steps starting from commercially available N-protected amino acids. In a metal-free and practical method, a catalytic amount of trifluoromethanesulfonic acid was sufficient to generate morpholinones under mild reaction conditions in an intramolecular hydroamination reaction in good to excellent yields.
Keywords: amino acids; cyclization; hydroamination; morpholinone; trifluoromethanesulfonic acid